Main Dimensions Characteristic of Purse Seine Fishing Vessel in Lempasing Coastal Fishing Port Lampung Province - Desmi Guritno; Ririn Irnawati; Adi Susanto (Jurnal Perikanan dan Kelautan, 2016)
Measurement of the main dimensions of the vessel is very important to analyze thevalue at L/B, L/D and B/D which can affect to the strength, speed and stability.The limited information and data regarding the size at purse seine boats inLempasing fishing port can be an obstacle in the development of fishing activities.This research aims to describe and to analyze the characteristics, ratios andanalyze the relationship between the ratio of the main dimensions of purse seinevessels with engine power and purse seine nets that used in PPP Lempasing. Theresearch was conducted in February 2015-March 2016 at coastal fishing port ofLempasing. The method was used census and analyzed by descriptivecomparative. The results show the range of the main dimensions from 9.31 to18.50 meters of LOA, Bmax from 3.72 to 6,05 meters and Depth (D) from 0.82 to1.75 meters. The ratio of the main dimensions have a range 2.13 to 3.81 of L/B,the value of L/D from 7.69 to 13.46 and the B/D from 2.91 to 4.62. The ratio ofpurse seine has not been used in determining the engine power and the size offishing gear. The ratio of main dimension does not have a tendency relationship toengine power and fishing gear because fishermen have not considered it.